Study on the characteristics of salinity transport in 2D cross-section unconfined aquifer - Hoang, Nguyen Van; Cong, Nguyen Thanh; Hoa, Pham Lan; Tung, Le Thanh (Vietnam Journal of Earth Sciences, 2016)
Groundwater salinity is currently a problem of a great concern in coastal areas of Vietnam. The characteristics of the salinity transport in 2-dimensional cross section of aquifer under different boundary conditions, boundary values and groundwater flow velocity field have been determined through finite element modeling application. Two aquifer types have been considered: confined aquifer with constant velocity in space and unconfined aquifer with variable horizontal and vertical velocity in space. The influence of the boundary types and boundary values on the salinity transport had been concentrated and analyzed. The results of the salinity distribution configuration within the aquifer have significance in directional research of the actual problems. The similar salinity distribution of two cases: constant specified boundary and variable specified boundary the average of which is equal to the constant specified value had given opportunity to simplify complicated actual problems for utilization of simpler models. References Nguyễn Văn Cư (chủ biên), 1999: Điều tra cơ bản tài nguyên môi trường nhằm khai thác hợp lí đất hoang hoá các bãi bồi ven biển cửa sông Việt Nam. Đề án điều tra cơ bản cấp nhà nước, Viện Địa lí, Hà Nội. Nguyễn Văn Cư, Phạm Huy Tiến, 2003: Sạt lở bờ biển miền Trung Việt Nam. Nxb. KH&KT Hà Nội, 200trg. Phạm Văn Hùng, Vũ Thị Thu Hoài, 2009: Đặc điểm địa mạo động lực vùng cửa sông ven biển từ cửa Ba Lạt đến cửa Đáy. Tạp chí Các Khoa học về Trái đất, T.31, (3), Hà Nội. Nguyễn Văn Hùng, 2002: Đặc điểm cơ bản của đứt gãy Tân kiến tạo khu vực Tây Bắc. Luận án Tiến sĩ, Viện Địa chất, Hà Nội. Hoàng Ngọc Quang (chủ biên), 2008: Nghiên cứu quản lý tổng hợp tài nguyên và môi trường lưu vực sông Mã. Báo cáo đề tài cấp Bộ Tài nguyên và Môi trường, Hà Nội. Phạm Quang Sơn, Nguyễn Tiến Công, Vũ Thị Thu Hoài, 2007: Diễn biến vùng ven biển các tỉnh Nam Định, Ninh Bình trước và sau khi có công trình thủy điện Hòa Bình qua phân tích thông tin viễn thám và GIS. Tạp chí Các Khoa học về Trái Đất. T.19, 3, tr.267-276. Nguyễn Thế Thôn, 1994: Chuyển động tân kiến tạo và hiện đại của dải ven biển và ven bờ từ Móng Cái đến Cửa Hội. Tạp chí Địa Chất, Loạt A, số 223, tr.1-6. Phạm Huy Tiến (chủ biên), 2004: Dự báo hiện tượng xói lở - bồi tụ bờ biển cửa sông và các giải pháp phòng tránh. Báo cáo tổng kết đề tài KHCN cấp Nhà nước KC-09-05. Viện Địa lý, Viện KH&CNVN, Hà Nội.